Transition from Pediatric to Adult Health Care for Dravet Syndrome Patients - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators from University Hospital of Rennes; Necker Hospital, Paris; and University Paris Descartes, France used a questionnaire to study the transition and transfer from pediatric to adult health-care system in patients with Dravet syndrome and their families.